Superoxide dismutase down regulation in osteoarthritis progression and end-stage disease - Scott, Jenny L. (2010)
OBJECTIVE: Oxidative stress is proposed as an important factor in osteoarthritis (OA). We therefore investigated the expression of the three superoxide dismutase (SOD) antioxidant enzymes in OA. METHODS: SOD expression was determined by real-time polymerase chain reaction and immunohistochemistry using human femoral head cartilage. SOD2 expression in Dunkin Hartley guinea pig knee articular cartilage was determined by immunohistochemistry. The DNA methylation status of the SOD2 promoter was determined using bisulfite sequencing. RNA interference was used to determine the consequence of SOD2 depletion on the levels of reactive oxygen species (ROS) using MitoSOX™ and collagenases, matrix metalloproteinase 1 (MMP-1) and MMP-13, gene expression. RESULTS: All three SOD were abundantly expressed in human cartilage but were markedly down-regulated in end-stage OA cartilage, especially SOD2. In the Dunkin Hartley guinea pig spontaneous OA model SOD2 expression was decreased in the medial tibial chondyle cartilage prior to, and following, the development of OA-like lesions. The SOD2 promoter had significant DNA methylation alterations in OA cartilage. Depletion of SOD2 in chondrocytes gave an increase in ROS but a decrease in collagenase expression. CONCLUSION: This is the first comprehensive expression profile of all SOD genes in cartilage and importantly, using an animal model, we show that a reduction in SOD2 is associated with the earliest stages of OA. We found that a decrease in SOD2 associates with an increase in ROS and but a reduction of collagenase gene expression, demonstrating the complexities of ROS function.